Romiplostim treatment for children with immune thrombocytopenia: Results of an integrated database of five clinical trials. Issue 11 (9th September 2020) - Tarantino, Michael D.; Despotovic, Jenny; Roy, John; Grainger, John; Cooper, Nichola; Beam, Donald; Raj, Ashok; Maschan, Alexey; Kim, June; Eisen, Melissa
Abstract: Background: Treatment for chronic immune thrombocytopenia (cITP) in children is largely limited to immunosuppressive agents. Thrombopoietin receptor agonists (TRAs) have been used to treat cITP in adults for over a decade. The objective of this integrated analysis was to examine the safety and efficacy of the TRA romiplostim in children with ITP. Methods: We examined efficacy and safety in children with ITP across five romiplostim trials: final data from two double‐blind placebo‐controlled trials and two open‐label extensions, and interim data from an ongoing single‐arm trial. Results: Patients (n = 24 initially placebo; n = 262 initially romiplostim) had a median age of 10.0 years (Q1: 6.0, Q3: 13.0), ITP duration of 1.9 years (Q1: 1.0, Q3: 4.0), and baseline platelet count of 14.3 × 10 9 /L (Q1: 7.5, Q3: 23.0). Among 282 patients receiving romiplostim, median treatment duration was 65 weeks (range 8‐471 weeks) and median weekly dose was 6.6 μg/kg (range 0.1‐9.7 μg/kg). Overall, 89% of romiplostim‐treated patients had platelet responses. Nineteen patients (7%) maintained treatment‐free responses for ≥6 months while withholding all ITP therapy. Grade 3 and 4 adverse events of bleeding occurred in 10% and <1% of romiplostim‐treated patients, respectively. Twenty‐five percent of patients had a serious adverse event, most commonly epistaxis (6%). Seven patients (2%) had neutralizing antibodies against romiplostim postbaseline and none had neutralizing antibodies against endogenous thrombopoietin. Efficacy and safety results appeared similar between children with ITP for ≤12 months and >12 months at baseline. Conclusions: Across five pediatric clinical trials, romiplostim was well tolerated. Most patients had a platelet response; some maintained responses for at least 6 months while withholding all ITP therapy.